2015
DOI: 10.17511/ijpr.2015.i04.14
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and health status of jenukuruba tribal children in Mysore district

Abstract: Introduction: Nutritional status is a sensitive indicator of community health and nutrition. It has an important role in determining health status especially in tribal children. Objective: This study was done to assess nutritional and health status among Jenukuruba tribal children in Mysore district. Methods: Community based cross sectional study done over a period of 2 years. 4207 children between the age group of 0-15 years of Jenukuruba tribal community were included. All data were recorded in a predesigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
1
0
3
Order By: Relevance
“…The commonly reported morbidities among children in our study were respiratory infections followed by skin infections and dental problems, which is in concordance with the findings from the study by Divakar et al 28 . In our study, only 5.3 per cent of the children had skin infections which are in contrast to that reported by Narayanappa et al 29 which reported skin infections in at least one-fifth of the children. It also reported a substantial proportion of children to be having dental problems (68.4%), while only 7.4 per cent had dental problems in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The commonly reported morbidities among children in our study were respiratory infections followed by skin infections and dental problems, which is in concordance with the findings from the study by Divakar et al 28 . In our study, only 5.3 per cent of the children had skin infections which are in contrast to that reported by Narayanappa et al 29 which reported skin infections in at least one-fifth of the children. It also reported a substantial proportion of children to be having dental problems (68.4%), while only 7.4 per cent had dental problems in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of our study showed that almost 42.3 per cent of children aged ≤5 yr had a low weight for age, 30.8 per cent had a low height for age and 15.4 per cent had a low weight for height which is supported by the study findings of Divakar et al 28 (45.03% of under-five children being malnourished) and Narayanappa et al 29 (33.1% and 35.7% of Jenukuruba tribal children having low height for age and low weight for age respectively). Furthermore, the prevalence of undernutrition among 6-17 yr old children was found to be 57.3 per cent (<−2SD BMI for age and gender centile) in our study, which is much higher than that reported from a nationwide survey in which it ranged from 18-30 per cent among 5-19 yr old tribal children and adolescents 4 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations